1968
DOI: 10.1107/s0567740868004644
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of WCl6

Abstract: A WCI6 compound, isostructural with UCI6, has been identified by comparing calculated intensities with Debye-Scherrer patterns.During the examination of a commercial~ preparation of supposed WCIs, the material was submitted for X-ray analysis to verify the compound designation. Chemical analyses were inconclusive in determining the W:CI ratio because of difficulties with the reactivity of the compound. With the Debye-Scherrer techniques used, the pattern proved unidentifiable with any other tungsten-chlorine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1974
1974
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The β-form has two tungsten atoms and three chlorine atoms within the asymmetric unit. The three chlorine sites have similar W–Cl bond lengths (2.23, 2.26, and 2.34 Å) and comparable Cl–W–Cl bond angles (91.3, 91.6, and 90.3°), resulting in a slightly distorted octahedral arrangement of chlorine atoms about the central tungsten atom . Both forms feature hexagonal close packed lattices of chlorine atoms with tungsten ions filling the octahedral holes.…”
Section: Resultsmentioning
confidence: 99%
“…The β-form has two tungsten atoms and three chlorine atoms within the asymmetric unit. The three chlorine sites have similar W–Cl bond lengths (2.23, 2.26, and 2.34 Å) and comparable Cl–W–Cl bond angles (91.3, 91.6, and 90.3°), resulting in a slightly distorted octahedral arrangement of chlorine atoms about the central tungsten atom . Both forms feature hexagonal close packed lattices of chlorine atoms with tungsten ions filling the octahedral holes.…”
Section: Resultsmentioning
confidence: 99%
“…Taylor and Wilson reported the structure of WCl 6 in 1974 with the correct z ‐coordinate of the W(2) atom, but seem not to have noticed the difference to the U(2) coordinate in their original report on UCl 6 . A previous report from 1968 gave the wrong z ‐coordinate . Only recently, the correct single‐crystal structure of β‐WCl 6 was published, whereas a structure refinement based on powder X‐ray data assumed WCl 6 to be isotypic to the wrong UCl 6 structure .…”
Section: Resultsmentioning
confidence: 99%
“…[28] Ap revious report from 1968 gave the wrong z-coordinate. [29] Only recently,t he correct single-crystal structureo fb-WCl 6 was published, [27] whereas as tructure refinement based on powder X-ray data assumed WCl 6 to be isotypic to the wrong UCl 6 structure. [30] We carried out aq uantumc hemical structuralo ptimization on WCl 6 starting with wrong atom coordinates for W(2) (z = 0.52, DFT-PBE0-D3/TZVP level of theory).…”
Section: Quantum Chemical Calculationsonr T-uclmentioning
confidence: 99%
“…Although a phase change at 228°C had been observed by Liempt (1931), the structure of the second polymorph of WC16 was not investigated until recently (Smith, Landingham, Smith & Johnson, 1968). These authors found a hexagonal polymorph of WC16 with a=10.511 (3) A and c=5.757 (1) A, (Table 1), the cell being similar to that of UCI6 which has the hexagonal space group P3ml and a= 10.…”
Section: Introductionmentioning
confidence: 84%
“…As a rough guide, the ratio (bw)2/(6 2 2 bc, +bw) is only 4 %, whereas in the X-ray case, the corresponding ratio is about 75%. It was therefore considered worth while to determine the parameter z-W(2) by a refinement of the X-ray powder data of Smith, Landingham, Smith & Johnson (1968).…”
Section: X-ray Refinementmentioning
confidence: 99%